دراسة ادمصاص الفوسفور على ترب متباينة المحتوى من كربونات الكالسيوم من المنطقة الساحلية (Latakia University Journal -Biological Sciences Series, 2019)
تحتل دراسات ادمصاص الفوسفور أهمية بالغة، إذ تهدف إلى تنظيم العمليات السمادية لتحقيق الإنتاج الأعظمي للمحاصيل. نفذت هذه الدراسة على 23 تربة متباينة في محتواها من كربونات الكالسيوم في المنطقة الساحلية عن طريق إنشاء منحنيات الادمصاص المتساوية الدرجة وتطبيق نموذجي لانغموير وفرويندليش للادمصاص، بينت هذه الدراسة أن نموذج فرويندليش كان أفضل في وصف العلاقة بين كمية الفوسفور المدمصة والتركيز التوازني، وذلك من نموذج لانغموير، وهذا يتضح استناداً إلى قيم متوسط معاملات الارتباط (R2) (0.896, 0.683) على الترتيب، وبرز دور استخدام دليل ادمصاص الفوسفور في توضيح أثر خصائص التربة على ثوابت الادمصاص، فكانت علاقته معنوية مع المحتوى العضوي والطيني الفيزيائي للتربة (0.599، -0.436) بالترتيب، ولم تكن معنوية مع محتوى التربة من كربونات الكالسيوم الكلية الذي يمكن أن يعزى إلى غلبة ظاهرة الترسيب على الادمصاص خصوصاً في ظل تراكيز فوسفورية مرتفعة. Studying phosphorus adsorption is a growing environmental concern to regulators and planners of nutrient management plans. P sorption characteristics and their relationship to soil properties were determined in 23 soil samples located in coastal region of Syria which are varied in calcium carbonate content. Phosphorus adsorption was studied by construction of adsorption isotherms, and by the use of Langmuir and Freundich models. The main achieved results were Freundlich model describing according to the coefficient correlation (Average R2 = 0.90) phosphorus adsorption better than Langmuir model (Average R2 = 0.68). Results showed the Phosphorus sorption is significantly related with organic matter content and clay content (r=0.599** and r= - 0.436*) respectively, but not significantly related with total CaCO3 which is could be due to the predominance of the precipitation on the sorption reactions especially under high- added concentrated phosphorus conditions  .